Identification and experimental validation of hub genes underlying depressive-like behaviors induced by chronic social defeat stress - Chen, Yexiang; Jiang, Yunhao; Jiang, Xingcong; Zhai, Caiyu; Wang, Yifei; Xu, Chi (Frontiers in Pharmacology, 2024)
Introduction: Major depressive disorder (MDD), characterized by severe neuropsychiatric symptoms and significant cognitive deficits, continues to present both etiological and therapeutic challenges. However, the specific underlying mechanisms and therapeutic targets remain unclear. Methods: We analyzed human postmortem dorsolateral prefrontal cortex (dlPFC) samples from MDD patients using datasets GSE53987 and GSE54568, identifying three key genes: AGA, FBXO38, and RGS5. To model depressive-like behavior, we employed chronic social defeat stress (CSDS) and subsequently measured the expression of AGA, FBXO38, and RGS5 in the dlPFC using qPCR and Western blot analysis following CSDS exposure. Results: CSDS significantly induced depressive-like behavior, and both the protein and transcriptional expression levels of AGA, FBXO38, and RGS5 in the dlPFC of mice were markedly reduced after stress, consistent with findings from datasets GSE53987 and GSE54568. Conclusion: Our research suggests that AGA, FBXO38, and RGS5 are potential biomarkers for MDD and could serve as valuable targets for MDD risk prediction.